Management Inventory Control and Assessment of Information Systems Based on ISO 25010 Test - Lestari, Arum Prayudi; Devi, Yesica Novrita; Arninputranto, Wibowo; Sari, Devina Puspita (IPTEK, DRPM, Institut Teknologi Sepuluh Nopember, 2024)
A shipyard company certainly has a recording system to manage raw material inventory. The minimum-maximum stock level method analysis was used to calculate raw material inventory control. The calculation results obtained using the min-max stock level method, amounting to 14 items of fiberglass ship raw materials, were calculated, and the resin has the highest utilization value. The ending stock in 2022 for the resin is 195 liters, while the calculated safety stock is 2.08 liters. The Min-Max Stock Level method has not been implemented in the company’s raw material inventory. A website-based system is used to control the inventory system. Inventory system development is needed so that the inventory management system in the company runs effectively and efficiently. The quality of system development can be measured based on the ISO 25010 standard feasibility test. Based on three aspects of the ISO 25010 standard, the test results show the percentage results based on the functional suitability aspect of 100% for each validator, which means the percentage in the system criteria is acceptable. In the usability aspect, the percentage obtained is 92.2%, indicating that the designed system’s quality is included in the feasible criteria. In eight, the maintainability aspect of the inventory management information system is included in the easy-to-maintain category. The system assessment results based on ISO 25010 can be summarized as follows.